Social partners and gender equality in Europe - Weber, Tina; Mantouvalou, Katerina; Bianchini, Danilo (Luxembourg, 2014)
"This report assesses the role of the social partners in advancing gender equality in Europe. It explores the actions taken within the different national frameworks of industrial relations and against the ranking of the Member States on the Gender Equality Index. Overall, significant actions are being taken by European and national social partner organisations and companies in support of gender equality. These tend to put the emphasis on campaigning and educational activities and the integration of work–life balance measures in national policies or collective agreements. The research also shows that while national peak-level social partner organisations have implemented a limited number of initiatives aimed at improving their internal gender equality performance, the representation of women in decision-making remains relatively weak."